Predictors of treatment initiation for alcohol use disorders in primary care. (1st October 2018) - Watkins, Katherine E.; Ober, Allison; McCullough, Colleen; Setodji, Claude; Lamp, Karen; Lind, Mimi; Hunter, Sarah B.; Chan Osilla, Karen
Highlights: In addition to need, patient factors predicted primary-care based alcohol treatment. Previously talking with a professional predicted subsequent treatment. Receiving brief therapy may help patients accept pharmacotherapy. Being homeless was a negative predictor of primary-care based alcohol treatment. Abstract: Background: We identified predictors of receiving treatment (brief therapy [BT] and/or extended-release injectable naltrexone [XR-NTX]) for the treatment of alcohol use disorders (AUDs) in primary care. We also examined the relationship between receiving BT and XR-NTX. Methods: Secondary data analysis of SUMMIT, a randomized controlled trial of collaborative care. Participants were 290 individuals with AUDs who reported no past 30-day opioid use and who were receiving primary care at a multi-site Federally Qualified Health Center. Bivariate and multivariate analyses examined predictors of BT and/or XR-NTX. Results: Thirty-two percent (N = 93) received either BT or XR-NTX, 28% (N = 82) received BT and 13% (N = 37) received XR-NTX; 9% (N = 26) received both BT and XR-NTX. Older age, white race, talking with a professional about alcohol use and having more negative consequences all predicted receipt of evidence-based treatment; being homeless was a negative predictor. The predictors of receiving BT included not being homeless and previously talking with a professional; the predictors of receiving XR-NTX included older age, white race and experiencing more negative consequences. In 80% of those who received both BT and XR-NTX, receipt of BT preceded XR-NTX. Conclusions: Patient factors were important predictors of receiving primary-care based AUD treatment and differed by type of treatment received. Receiving BT was associated with subsequent use of XR-NTX and may be associated with a longer duration of XR-NTX treatment. Providers should consider these findings when considering ways to increase primary-care based AUD treatment.